Can They Make It on Their Own? Hosts, Microbes, and the Holobiont Niche - Kopac, Sarah M.; Klassen, Jonathan L. (Frontiers in Microbiology, 2016)
Virtually all multicellular organisms host a community of symbionts composed of mutualistic, commensal, and pathogenic microbes, i.e., their microbiome. The mechanism of selection on host-microbe assemblages remains contentious, particularly regarding whether selection acts differently on hosts and their microbial symbionts. Here, we attempt to reconcile these viewpoints using a model that describes how hosts and their microbial symbionts alter each other’s niche and thereby fitness. We describe how host-microbe interactions might change the shape of the host niche and/or reproductive rates within it, which are directly related to host fitness. A host may also alter the niche of a symbiotic microbe, although this depends on the extent to which that microbe is dependent on the host for reproduction. Finally, we provide a mathematical model to test whether interactions between hosts and microbes are necessary to describe the niche of either partner. Our synthesis highlights the phenotypic effects of host-microbe interactions while respecting the unique lifestyles of each partner, and thereby provides a unified framework to describe how selection might act on a host that is associated with its microbiome.